Preparation of Soluble Complex of Curcumin for the Potential Antagonistic Effects on Human Colorectal Adenocarcinoma Cells - Jamal Moideen Muthu Mohamed; Ali Alqahtani; Barkat A. Khan; Adel Al Fatease; Taha Alqahtani; Krishnaraju Venkatesan; Fazil Ahmad; Bashar I. Alzghoul; Ali Alamri (MDPI AG, 2021)
This study was designed to investigate the effects of curcumin (CMN) soluble complex (SC) prepared by melt casting (HM) and hot-melt extrusion (HME) technology. Phase solubility (PS) study, in silico molecular modeling, aqueous solubility, drug release, and physicochemical investigation including a novel dyeing test was performed to obtain an optimized complex by a central composite design (CCD). The results show that the HME-SC produces better improvements towards solubility (0.852 ± 0.02), dissolution (91.87 ± 0.21% at 30 min), with an ideal stability constant (309 and 377 M−1 at 25 and 37 °C, respectively) and exhibits AL type of isotherm indicating 1:1 stoichiometry. Intermolecular hydrogen bonding involves the formation of SC, which does not undergo any chemical modification, followed by the complete conversion of the amorphous form which was identified by XRD. The in vitro cytotoxicity showed that IC50 was achieved in the SW480 (72 µM.mL−1) and Caco-2 (40 µM.mL−1) cells while that of pure CMN ranged from 146 to 116 µM/mL−1. Apoptosis studies showed that cell death is primarily due to apoptosis, with a low rate of necrosis. In vivo toxicity, confirmed by the zebrafish model, exhibited the safety of the HME-SC. In conclusion, the HME-SC potentially enhances the solubility and cytotoxicity to the treatment of colorectal cancer (CRC).